(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2018)
يهتم علم اجتماع التنمية ، وكذلك سوسيولوجيا الثقافة ، بالتمييز وترسيم الحدود الدقيقة الفاصلة بين كل من مفهومي النمو والتنمية . ذلك أن خطر الخلط بين المفاهيم المتجاورة في المعنى أو الدلالة لا ينحصر في دائرة النظر والتحليل ، وإنما يتعداه إلى حقل الفعل في الواقع ، لطالما النظرية مدخل العمل والممارسة . فالتنمية مشروع تاريخي يعمد إلى تغيير الواقع الاجتماعي القائم مدخلاً إلى بناء واقع آخر بديل أكثر تقدماً ومدنية على سلم تطور المجتمعات البشرية . في حين أن النمو هو مجرد حدث اقتصادي طارئ أو حالة اقتصادية وضعية ومتغيرة . وبالتالي ، فإن التنمية مسألة بنيوية تستوجب تغييرات اقتصادية وسياسية وثقافية نوعية ، فيما النمو حالة تغير كمي أو تقني لا يقتضي ، بالضرورة ، مثل هذه التغييرات الأخيرة . وتبعاً لذلك ، فقد رأينا ، التزاماً بمبادئ المنهج الجدلي التاريخي ضمن الإطار العام لمدرسة التبعية ، أن الخلط بين هذين المفهومين وممارسة التنمية وكأنها مجرد نمو ، فقط ، وذلك في عموم بلداننا العربية ، هو السبب الخطير الذي يكمن وراء الفشل الذي انتهت إليه اليوم معظم تجارب التنمية المزعومة في تلك البلدان . وبالتالي ، فإن الوعي بحقيقة أن التنمية قضية هيكلية هو منطلق الشروع بمشروع تنمية فعلية وإيجابية . Development sociology, like the sociology of culture, focuses on drawing the minute line between the concepts of growth and development. Confusing these semantically interrelated concepts is not only confined to the scope of theory and analysis, but also goes well beyond it to cover the field of action in reality, since action is the key to theory and practice. Development, then, is a historical enterprise for changing the existing social reality and building a gateway to another more advanced, peaceful, and civilized alternative on the ladder of development for human societies. While growth is just an accidental economic event or a variable economic state of emergency, development requires structural economic changes, political and cultural quality. Growth in the case of technical or quantitative change does not necessarily require such changes. Accordingly, following a commitment to the principles of dialectical historical approach within the overall framework of the School of Subsidiarity, we have seen that confusing these two concepts and using development and growth as if they were just growth- this being the case in most Arab countries- is the critical reason lying behind the failure of the alleged development experiments in these countries. Thus, awareness of the fact that development is a structural issue forms the basis of a positive and effective development project.